Modeling of the process of territorial communities formation using swarm intelligence algorithms - Lytvyn, Vasyl; Uhryn, Dmytro; Nadiein, Nazarii; Кlichuk Oleg (Technology audit and production reserves, 2017)
The process of TC formation is considered, using algorithms of swarm intelligence. The main aim of TC formation is reducing the budget and saving the public funds. The approved methodology and the process of formation of capable communities are studied when in the human settlements that form the society is the administrative building, the health care institution, the general education school of the third degree, the kindergarten, the institutions of social protection, housing and communal services, taking into account the financial security and daily migration of residents in the zone of accessibility of the administrative center. The minimum distance from the center of the community to other settlements is taken for the purpose of forming territorial communities. A mathematical model of such problem is developed, using specific limitations that arise from the formulation of the problem itself. To build effective algorithms for formation of territorial communities, the concept of independence of communities, as well as the contiguity of individual councils is introduced. Stochastic algorithms of ant colony and migrating birds have been adapted to solve the established multicriteria optimization problem. The proposed approach is investigated.